The impact of unlisted and no-landline respondents on non-coverage bias: The Italian case - Emanuela Sala; Roberto Lillini (University of Essex, Institute for Social and Economic Research (ISER), 2014)
To survey the general population, survey agencies often use sampling frames of landline numbers. However, these frames may exclude a relevant share of the target population. In 2012, 50% of Italian adults are excluded from the sampling frame, as they are unlisted (UN) or do not own a landline telephone (NT). Using a unique national survey with full-coverage of the Italian population, our study describes the changes in the composition of landline telephone coverage over time and investigates differences in demographic and socio-economic characteristics between (i) respondents included in and excluded from the sampling frame and (ii) NT and UN respondents. It also explores whether these differences lead to under-coverage bias and evaluates the impact of current post-adjustment strategies on the total under-coverage bias as well as on its two components separately.
Keywords: C81; C83; D72; 330; Telephone surveys; coverage error; bias in telephone surveys